PERENCANAAN PROGRAM KEGIATAN RESPONSIF GENDER - Novan Ardy Wiyani (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2017)
Abstract: This paper is structured to provide a description of the planning of gender responsive early childhood programs. The hope is that gender responsive early childhood education programs can shape and develop a gender equitable early childhood outlook. This can be done by preparing a gender responsive early childhood program planning. There are three designs of gender responsive early childhood programs. First, the design of the gender responsive thematic program planning. In this planning design, teachers conceived two gender-responsive themes, namely the theme of my profession and the theme of my hero. Second, the design of gender responsive habits planning program. In this planning design teachers conduct routine annual habituation activities by carrying out carnival activities in order to commemorate the independence day of the Republic of Indonesia and carry out the commemoration activities of Kartini Day. Third, the design of gender responsive parent involvement program planning. There are three design activities in this planning design, namely father day, cooking day, and my father is my teacher.Keywords: planning, activities, early childhood, gender Abstrak: Tulisan ini disusun untuk memberikan deskripsi tentang perencanaan program kegiatan PAUD responsif gender. Harapannya, program kegiatan PAUD responsif gender dapat membentuk dan mengembangkan pandangan pada anak usia dini yang adil gender. Hal itu dapat dilakukan dengan menyusun perencanaan program kegiatan PAUD responsif gender. Ada tiga desain perencanaan program kegiatan PAUD responsif gender. Pertama, desain perencanaan program pembelajaran tematik responsif gender. Pada desain perencanaan ini guru PAUD memunculkan dua tema yang responsif gender, yaitu tema profesiku dan tema pahlawanku. Kedua, desain perencanaan program pembiasaan responsif gender. Pada desain perencanaan ini guru PAUD melaksanakan kegiatan pembiasaan rutin yang bersifat tahunan dengan melaksanakan kegiatan karnaval dalam rangka memperingati hari kemerdekaan Republik Indonesia dan melaksanakan kegiatan peringatan hari Kartini. Ketiga, desain perencanaan program pelibatan orang tua responsif gender. Ada tiga desain kegiatan pada desain perencanaan ini, yaitu father day, cooking day, dan my father is my teacher.Kata kunci: perencanaan, kegiatan, anak usia dini, gender